2010
DOI: 10.1017/s0025315410000032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substratum colour on the recruitment of macrofouling communities

Abstract: Settlement of the fouling community is generally influenced by the physical, chemical and biological properties of the settling surface. The colour of the substratum may also exert an influence on larval settlement. In the present study, the influence of surface colour on the recruitment of fouling communities was investigated by suspending acrylic panels (red, green, blue, white and yellow) in coastal waters. Results showed that the colour of the substratum plays an important role in the recruitment of sessil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 24 publications
4
16
0
Order By: Relevance
“…5). These results are in accordance with previous studies (Hurley 1973; Satheesh and Wesley 2010; Dobretsov et al 2013) in which barnacles settled most abundantly on dark surfaces (blue, red, black). Significantly lower densities of Balanus improvisus were found on panels on which the algae Ulva and Cladophora were present ( p  = 0.036 and 0.049, respectively), indicating possible competition for space between these species.
Fig.
…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…5). These results are in accordance with previous studies (Hurley 1973; Satheesh and Wesley 2010; Dobretsov et al 2013) in which barnacles settled most abundantly on dark surfaces (blue, red, black). Significantly lower densities of Balanus improvisus were found on panels on which the algae Ulva and Cladophora were present ( p  = 0.036 and 0.049, respectively), indicating possible competition for space between these species.
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…Similar observations were made by Satheesh and Wesley (2010) in India, where the highest biofouling during the summer season was on blue and red panels, compared to white or yellow ones. Swain et al (2006) also showed the importance of surface colour in short-term testing of antifouling paints, with black panels being the most heavily fouled.…”
Section: Resultssupporting
confidence: 87%
“…Amphibalanus improvisus (Darwin, 1854), for example, prefers relatively smooth surfaces (Berntsson et al 2000(Berntsson et al , 2004 and this could be due to the antennular adhesive disc, which needs a specific level of roughness to attach firmly (Nott & Foster 1969;Yule & Walker 1984;Berntsson et al 2000). On the other hand, other species are completely unaffected by roughness: the settlement of cyprids of S. balanoides was tested for 15 different rock types, resulting to be independent of any potential effect of surface roughness or colour cues (Holmes et al 1997), while for A. amphitrite (= Balanus amphitrite) a preference for red and blue acrylic sheets was demonstrated (Satheesh & Wesley 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm composition and larval settlement are known to be affected by the physical properties of a substrate, such as colour (Satheesh and Wesley, ), surface roughness (Kerr and Cowling, ), wettability (Maki et al ., ) as well as topography (Magin et al ., ). However, only limited information is currently available on the interactions between the physical properties of a substrate, biofilm formation and subsequent larval settlement.…”
Section: Biofilms and Macrofouling: A Love/hate Affairmentioning
confidence: 99%